Decision-Making at End-of-Life for Children With Cancer: A Systematic Review and Meta-Bioethical Analysis - Juárez-Villegas, Luis Enrique; Altamirano-Bustamante, Myriam M.; Zapata-Tarrés, Marta M. (Frontiers in Oncology, 2021)
Background: Evidence show that medical education includes a variety of skills going from basic to clinical aspects. Facts show that ethical and human values are not considered in the medical school curricula, and this is evident in medical practice in some scenarios as decision-making at the end-of-life of pediatric cancer patients. Methods: This study explores Bioethical approach to address complex decision making at the end-of-life in children and adolescent with cancer. We are a cross-functional group of scientists from several academic disciplines which conducted a systematic review using a variant of the PICO and PRISMA approach. The search was carried out in five databases, resulting in 10 research papers. Followed by quality screenings, 7 articles were finally selected for further exhaustive meta-bioethical analysis. Results: Our focus is on the state of the art in order to understand the bioethical deliberation at the end of life in pediatric oncology. Here we report a systematic review that include (i) classification of the screened articles by the type of decision-making they use, ii) the system values that are at the stake in the decision making at the end-of-life and iii) bioethical and ethical discernment queries. We end with a discussion about the best practice of ethical discernment and decision making at the end of life. This study highlights the need to develop more research to better understanding of the influence and origin of these multidimensional factors which determine critical decisions that defines the quality of life of patients in a sensitive moment. Conclusion: Our conclusion includes the fact that personal aspects of the physician define action more over that knowledge or organized structure. It is mandatory that pediatric oncologist receive an ethic and humanistic education.